A 90-DAY ORAL SAFETY ASSESSMENT OF AQUEOUS GINGER EXTRACT ON SOME VITAL ORGANS IN RATS - Yakubu, Musa Itopa; Danbala, Ahmed A.; Timothy, Micah; Abbas, Medinat Yakubu; Sambo, Safiya S.; Chindo, Ben A. (FUDMA JOURNAL OF SCIENCES, 2024)
Zingiber officinale (Ginger), similar to other medicinal plants is generally believed to be safe because is natural. However, several studies have shown that some medicinal plants are toxic to vital organs. This study was conducted to investigate the potential toxic effect of aqueous extract of ginger on vital organs in Wistar rats. Eighty Wistar rats divided into four groups of 20 rats each (10 females and 10 males) were used. The rats in the treatment groups were administered ginger extract daily at doses of 500, 1,000 and 2,000 mg/kg for 90 days, while those in the control group were given distilled water. On the 91st day, the rats were euthanized and blood samples collected for biochemical analysis. Their vital organs were dissected, removed, weighed and fixed in 10% formalin for histopathological assessment.  The remaining rats were kept and observed for 14 days for any persistence or reversibility of toxic effects. The ginger extract did not produce any significant changes in the relative organ weights of the heart, liver, kidney, lungs, brain, thyroid glands, uterus and testes of the rats. However, significant increase in blood urea; and serum electrolytes (sodium, potassium, and bicarbonate) were observed. Histopathological assessment showed various pathological lesions in most of the organs at doses of 1,000 and 2,000 mg/kg.  However, after a 14-day recovery period, the observed changes were reversed. The findings showed that repeated administration of aqueous ginger extract for 90 days at high doses could induce organ toxicities that are reversible after 14 days.